2007
DOI: 10.1177/0895904807307066
|View full text |Cite
|
Sign up to set email alerts
|

The Passage of Education Citizen Initiatives

Abstract: In recent years, many critical education policy reforms across the American states have been attempted through citizen ballots. This study examines citizens' voting behavior on three salient education initiatives proposed in California. Analyses of exit poll data indicate that voting on education initiatives is greatly influenced by ideological predispositions, self-interest, and racially based incentives. Local school districts' conditions become more influential once we examine voting separately across racia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Bali's (2008) research study suggests that a voter's ideology and racial/ethnic background drive the passage of initiative-based reforms to education. This evidence suggests that the broad dissemination of information about the issues may not be sufficient to influence voters.…”
Section: Implications For Policymakers Researchers Public Debate Amentioning
confidence: 99%
“…Bali's (2008) research study suggests that a voter's ideology and racial/ethnic background drive the passage of initiative-based reforms to education. This evidence suggests that the broad dissemination of information about the issues may not be sufficient to influence voters.…”
Section: Implications For Policymakers Researchers Public Debate Amentioning
confidence: 99%
“…Age has also been shown to affect views on vouchers, with older citizens generally less supportive of school vouchers (Leal, ; Moe, ). Parents are more supportive of vouchers than nonparents (Bali, :446; Moe, :211). Based on survey data, Moe found that respondents who were Catholic or born‐again Christians were more supportive of vouchers, and people with less income and less education were more supportive of vouchers (2001:214–15).…”
Section: The Bases Of Support For and Opposition To School Vouchersmentioning
confidence: 99%
“…Based on prior studies, we expect partisanship to be an important factor in voter support for school vouchers (Bali, ; Brunner and Imazeki, ). We expect school vouchers to appeal more to Republicans and conservatives, who are especially likely to believe that the free market is better able to provide effective educational services than government (Engel, ).…”
Section: The Bases Of Support For and Opposition To School Vouchersmentioning
confidence: 99%
“…But in these other fields, national leaders and funders placed a greater priority on the independent study of factors affecting decision makers' judgments, particularly the political factors. Studies in these other fields not only examined the impact of governmental decision making (Martin 2008;DeBray-Pelot and McGuinn 2009;Scott, Lubienksi, and DeBray-Pelot 2009) but also the major professions and other stakeholders such as teachers, business organizations, as well as grassroots organizations and public voting (Bali 2008;Cibulka and Myers 2008;Cooper and Randall 2008). 1 We believe that as a result, the research community in these other fields has a more grounded view of what types of research and what channels of presentation might more effectively influence policy makers' decisions.…”
mentioning
confidence: 99%